2020
DOI: 10.1097/ta.0000000000002811
|View full text |Cite
|
Sign up to set email alerts
|

How repetitive traumatic injury alters long-term brain function

Abstract: BACKGROUND How recurrent traumatic brain injury (rTBI) alters brain function years after insult is largely unknown. This study aims to characterize the mechanistic cause for long-term brain deterioration following rTBI using a rat model. METHODS Eighteen Sprague-Dawley wild-type rats underwent bilateral rTBI using a direct skull impact device or sham treatment, once per week for 5 weeks, and were euthanized 56 weeks after the first injury. Weekly rotaro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In contrast, diffuse moderate TBI did produce deficits in grip strength at 28 days post-injury, the latest time point assessed ( 32 , 33 , 101 ). For repeated mild injury, bilateral mTBI weekly for 5 weeks led to impaired grip strength at 40–45 weeks post-injury ( 100 ), whereas 3 impacts 24 h apart led to no deficits at 30 days post-injury, ( 99 ) with these the only time points assessed in these studies. Notably, with the negative result, the average of three trials relative to body weight was recorded ( 99 ), whereas the positive result was only one trial reported as maximum force achieved, introducing a potential confound ( 100 ).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…In contrast, diffuse moderate TBI did produce deficits in grip strength at 28 days post-injury, the latest time point assessed ( 32 , 33 , 101 ). For repeated mild injury, bilateral mTBI weekly for 5 weeks led to impaired grip strength at 40–45 weeks post-injury ( 100 ), whereas 3 impacts 24 h apart led to no deficits at 30 days post-injury, ( 99 ) with these the only time points assessed in these studies. Notably, with the negative result, the average of three trials relative to body weight was recorded ( 99 ), whereas the positive result was only one trial reported as maximum force achieved, introducing a potential confound ( 100 ).…”
Section: Resultsmentioning
confidence: 94%
“…Grip strength and fine motor ability were assessed via the grip strength meter ( 30 , 93 , 97 100 ), isometric pull task ( 33 , 101 ), pellet reaching tasking ( 34 ), and Montoya staircase test ( 94 ) ( Table 4 ). The grip strength meter requires minimal pre-training, whereas the other tasks involve more extensive training with food restriction, with the test relying on the animal's desire to obtain sugar pellets as a reward for completing the task successfully.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 80 % of TBIs sustained worldwide are mild in severity ( McCrory et al, 2013 ). Repetitive TBIs (rTBIs), even of mild severity, can prolong and worsen TBI secondary injury ( Fujita et al, 2012 ; Bailes et al, 2013 ; Fehily and Fitzgerald, 2017 ; Mouzon et al, 2018 ; Dhillon et al, 2020 ). Continual treatment of secondary injury is necessary for patients that suffer rmTBI as they may have an increased risk for neurodegeneration ( Faden and Loane, 2015 ; Edwards et al, 2017 ; Gao et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%